Using an Electronic Mindfulness-based Intervention (eMBI) to improve maternal mental health during pregnancy: results from a randomized controlled trial - Haßdenteufel, Kathrin; Müller, Mitho; Abele, Harald; Brucker, Sara; Graf, Johanna; Zipfel, Stephan; Bauer, Armin; Jakubowski, Peter Martin; Pauluschke-Fröhlich, Jan; Wallwiener, Markus; Wallwiener, Stephanie (Psychiatry research, 2023)
Prevalence rates of peripartum depression and anxiety are high and correlate with adverse maternal and neonatal outcomes. Mindfulness-based interventions (MBI) have been shown to reduce mental distress during pregnancy. A multicenter, randomized controlled study was conducted after screening for depressive symptoms. The intervention group (IG) was given access to an 8-week supervised eMBI between weeks 29 and 36 of pregnancy and followed up to 5 months postpartum. Psychometric data were collected using the Edinburgh Postnatal Depression Scale (EPDS), the State-Trait Anxiety Inventory (STAI), the Pregnancy-Related Anxiety Questionnaire (PRAQ-R), the Freiburg Mindfulness Inventory (FMI-14) as well as the Patient Health Questionnaire (PHQ). Out of 5299 pregnant women, 1153 scored >9 on the EPDS and N = 460 were included in the RCT. No significant interaction effects for depressive symptoms and anxiety were found. Pregnancy- and birth-related anxiety decreased significantly in the IG and 6 weeks after birth, the rate of women at risk for adverse mental outcome was significantly lower compared to the CG. Mindfulness scores improved significantly in the IG. The eMBI program did not show effective regarding general depressive or anxiety symptoms, however, positive results were demonstrated regarding pregnancy and birth-related anxiety and the prevention of postpartum depression.